Investigation the therapeutic effect of mindfulness-based cognitive-behavioral counseling in pregnant women with body image dissatisfaction: A randomized controlled trial - Mehnoosh Farahabadi; Abbas Amanollahi; Bahman Cheraghian; Zahra Abbaspoor (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Background and aims: Dissatisfaction with body image during pregnancy is a common issue in the general population and can pose risks for both the mother and the child. The aim of this study was to investigate the therapeutic effect of mindfulness-based cognitive-behavioral counseling in pregnant women with body image dissatisfaction: A randomized controlled trial. Methods: In this study, 50 pregnant women who were over 26 weeks pregnant were randomly assigned to intervention and control groups. In the intervention group, Mindfulness-based cognitive behavioral therapy was taught to pregnant women over 8 consecutive sessions, while the control group received no intervention. Body image concerns questionnaire was completed by both groups before and after the intervention, and data were analyzed using descriptive statistics and multivariate analysis of covariance. Results: The results showed that before the intervention, the mean and standard deviation of body image concern scores in the intervention group was 58.36 ± 3.13 and in the control group, was 58.08 ± 3.31, but after the end of the intervention, in the intervention group it decreased to 41.40 ± 2.85 (p < 0.001), while in the control group, it decreased (57.64 ± 3.42) slightly (P = 0.951). The total scores for body image concern in the intervention group were significantly lower compared to the control group (p < 0.001). Conclusion: Mindfulness-based cognitive behavioral therapy can help reduce body image concerns in pregnant women. Therefore, it is recommended that mental health professionals utilize this approach to improve the psychological and physical well-being of pregnant women and assist them in modifying their attitudes towards body image.